2021
DOI: 10.21203/rs.3.rs-1037441/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Related to Nurses and Physicians’ Knowledge of and Attitudes Towards Palliative Care

Abstract: Background With the increase of the elderly population, the need for palliative care has increased, which is one of the requirements of effective palliative care services, sufficient knowledge and positive attitude of nurses and physicians towards this care approach. The aim of this study was to determine the factors related to the knowledge and attitudes of nurses and physicians about palliative care. Methods This descriptive correlational study was performed in 2021 on 277 nurses and physicians working in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The results of the studies conducted in Iran show that nurses and nursing students do not have a positive attitude towards care provision for dying patients (Iranmanesh et al, 2009;Ashrafizadeh et al, 2022), and oncology and ICU nurses (Razban F, 2015a) as well as home care nurses have also a negative attitude towards PC (Dehghannezhad J, 2021). Studies have shown that nurses with a negative attitude towards PC avoid dealing with dying patients and transfer their fears, hopelessness and frustrations to the patient and his/her family.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the studies conducted in Iran show that nurses and nursing students do not have a positive attitude towards care provision for dying patients (Iranmanesh et al, 2009;Ashrafizadeh et al, 2022), and oncology and ICU nurses (Razban F, 2015a) as well as home care nurses have also a negative attitude towards PC (Dehghannezhad J, 2021). Studies have shown that nurses with a negative attitude towards PC avoid dealing with dying patients and transfer their fears, hopelessness and frustrations to the patient and his/her family.…”
Section: Introductionmentioning
confidence: 99%